2017
DOI: 10.1097/ccm.0000000000002313
|View full text |Cite
|
Sign up to set email alerts
|

Race, Ethnicity, Health Insurance, and Mortality in Older Survivors of Critical Illness

Abstract: Objective To determine whether minority race or ethnicity are associated with mortality and mediated by health insurance coverage among older (age ≥65 years) survivors of critical illness. Design A retrospective cohort study. Setting Two New York City academic medical centers. Patients A total of 1,947 consecutive white (1,107), black (361), and Hispanic (479) older adults who had their first medical-ICU admission from 2006 through 2009 and survived to hospital discharge. Interventions None. Measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
0
13
1
2
Order By: Relevance
“…We were unable to control for direct or surrogate measures of pre‐hospitalization disability (eg, admission from nursing home) or for preferences for life‐sustaining therapy at hospital discharge, both of which are important predictors of post‐hospitalization mortality in older ICU survivors . However, in our prior study of older ICU survivors from two New York City medical centers, after controlling for these variables, the HR of the association between Medicaid insurance and the post‐hospitalization mortality rate was greater than what we observed in this study …”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…We were unable to control for direct or surrogate measures of pre‐hospitalization disability (eg, admission from nursing home) or for preferences for life‐sustaining therapy at hospital discharge, both of which are important predictors of post‐hospitalization mortality in older ICU survivors . However, in our prior study of older ICU survivors from two New York City medical centers, after controlling for these variables, the HR of the association between Medicaid insurance and the post‐hospitalization mortality rate was greater than what we observed in this study …”
Section: Discussioncontrasting
confidence: 80%
“…[9][10][11]38 However, in our prior study of older ICU survivors from two New York City medical centers, after controlling for these variables, the HR of the association between Medicaid insurance and the post-hospitalization mortality rate was greater than what we observed in this study. 14 The Medicare Shared Savings Program for Accountable Care Organizations was implemented during the study period, and we were unable to adjust for how this new program may affect survivors of critical illness with different types of insurance. We also sought to examine the possibility of residual confounding with a quantitative bias analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This burden also impacts their caregivers, and is a serious problem that can cause psychological stress. A recent observational study conducted in two academic hospitals in New York City reported that race or ethnicity was not associated with long-term mortality among ICU survivors, while insurance status was closely associated 11. In other words, the lack of insurance coverage was associated with increased mortality among ICU survivors, and thus this study has emphasized the need for the provision of appropriate financial coverage for ICU survivors.…”
Section: Introductionmentioning
confidence: 76%
“…As ICU care requires substantial resources, and because some interventions can be unnecessary, harmful, or futile—particularly when caring for critically ill elderly patients—specific ICU treatment decisions are influenced by multiple factors, such as regional health care capacity, health insurance systems, and cultural and religious considerations. [1,29,30] However, our knowledge about critical care in different regional and cultural contexts is currently limited. [1] Further researches are required to address the effects of different cultural and regional backgrounds on critical care.…”
Section: Discussionmentioning
confidence: 99%